Hubungan Pengetahuan Anak tentang Dampak Penggunaan Gadget dengan Prestasi Belajar - Nurfauziah, Fitria (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2023)
Based on data from the Internet World Statistics (IWS) in 2019 Indonesia ranks 4th in the 20 most countries that use the internet with a total of 171,260,000 internet users. According to the study entitled "Digital Citizenship Safety among Children and Adolescents in Indonesia, at least 30 million children and adolescents in Indonesia are internet users, and most people access the internet using gadgets and sadis. Nowadays many children under 12 use gadgets not for learning or looking for information but to play games even though in fact the use of gadgets under 12 years is more dominant on negative impacts, such as radiation that can damage nerve tissue and brain and can cause eye health to decline.The purpose of this study is to determine the relationship of children's knowledge about the impact of using gadgets with learning achievement in Vth grade students at SDN Pakulonan Barat 1. Tangerang This research method is a quantitative study that uses primary data (questionnaire) and uses a cross sectional research method with the aim to find out the relationship between independent variables with the dependent variable, data collected using a questionnaire. The number of samples was 44 grade V students at SDN Pakulonan Barat 1 Tangerang in 2020. From the results of the study, it was found that children who had knowledge of the effects of using a good gadget as many as 35 respondents (80%) were associated with high learning achievement. Statistical test results obtained value (ρ-value = 0.018 <α 0.05), it can be concluded that there is a significant relationship between children's knowledge about the impact of the use of gadgets with learning achievement. Suggestions from the results of this study can be taken into consideration for institutions, especially for students in an effort to improve learning achievement by disseminating information about children's knowledge about the impact of using gadgets.